Use of adhesion-defective mutants of Staphylococcus aureus to define the role of specific plasma proteins in promoting bacterial adhesion to canine arteriovenous shunts - FOSTER, TIMOTHY (My University, 1995)
We used an ex vivo canine arteriovenous shunt model, previously developed to study plasma protein adsorption and thrombogenesis on polymeric biomaterials, to define the role of host proteins in promoting adhesion of Staphylococcus aureus. Either polyethylene or polyvinyl chloride tubings were exposed to canine blood for 5, 15, or 60 min at a flow rate of 300 ml/min and then were flushed in phosphate-buffered saline (PBS), cut into 1.5-cm segments, and stored at -70 degrees C. After thawing, each segment was preincubated in 0.5% albumin in PBS to prevent nonspecific staphylococcal attachment to surfaces that were not exposed to blood. Each segment was then incubated with 4 x 10(6) CFU of [3H]thymidine-labelled S. aureus per ml for 60 min at 37 degrees C in an in vitro adhesion assay. Two site-specific mutants of S. aureus were tested: one specifically defective in adhesion to surface-bound fibronectin (FnAd-def) and the other defective in adhesion to fibrinogen (FgAD-def) [corrected]. Compared with their respective parental strains, the FgAd-def, but not the FnAd-def, mutant of S. aureus showed a strong (> 80%) decrease in attachment to ex vivo tubings. The adhesion of each strain of S. aureus onto polyethylene was consistently more than twofold higher than the adhesion onto polyvinyl chloride segments exposed to flowing blood for 5 or 15 min, but adhesion became similar to that on polyvinyl chloride after 60 min of exposure. In conclusion, the specific adhesion-defective mutants of S. aureus suggested that fibrinogen was the most active adhesion-promoting protein in a short-term blood-material interaction. The experimental approach described in this study should prove useful for screening materials thought to be resistant to protein-mediated staphylococcal adhesion and colonization.